2022
DOI: 10.3390/medicina58081003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Delay in Acute Ischemic Stroke Care: Current Findings and Future Perspectives in a Tertiary Stroke Center from Romania—A Cross-Sectional Study

Abstract: Background and objectives: The time interval between stroke onset and hospital arrival is a major barrier for reperfusion therapies in acute ischemic stroke and usually accounts for most of the onset-to-treatment delay. The present study aimed to analyze the pre-hospital delays for patients with acute ischemic stroke admitted to a tertiary stroke center in Romania and to identify the factors associated with a late hospital arrival. Material and methods: The study population consisted of 770 patients hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
3
15
0
1
Order By: Relevance
“…To promote the earliest possible access to treatment, the evaluation of intervals between stroke onset and hospital arrival has been the subject of numerous studies (17,27,48,(63)(64)(65)] to determine the most appropriate interventions. They have produced divergent results, re ecting the methodological differences, cultural and educational differences of the populations studied, and differences in the health service organization in general and the stroke chain in particular.…”
Section: Discussionmentioning
confidence: 99%
“…To promote the earliest possible access to treatment, the evaluation of intervals between stroke onset and hospital arrival has been the subject of numerous studies (17,27,48,(63)(64)(65)] to determine the most appropriate interventions. They have produced divergent results, re ecting the methodological differences, cultural and educational differences of the populations studied, and differences in the health service organization in general and the stroke chain in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Workers' attitudes towards stroke victims are overall good in our series (score = 81.4%). However, the responses in relation to the item "behavior towards a person with stroke warning signs/symptoms" suggest that, during awareness campaigns, it is important to focus on the time of admission to hospital for stroke victims and its impact on brain cell life, treatment seeking, patient recovery and complications leading to sequelae and death [71] [72] [73] [74] [75]. The normal attitude of workers towards stroke victims could be explained by education and prior information about stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bystanders also play a critical role in shortening delay time after the onset of stroke, as they usually take action and call for help. Studies have found that presence of bystander was related to shorter delay among stroke patients (Terecoasă et al, 2022). Among demographic variables, several studies have explored the association between prehospital delay and age (Nagao et al, 2020; Wang et al, 2021), gender (Potisopha et al, 2020), education (Fladt et al, 2019; Nepal et al, 2019), and income (Niklasson et al, 2019; Wang et al, 2021); however, inconsistent and weak associations were reported among those demographic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Among clinical factors, studies have frequently reported an association between increased stroke severity diagnosis or the degree of neurologic deficit and shorter prehospital delay (Wannarong et al, 2019). Some health conditions associated with early arrival were related to specific risk factors (atrial fibrillation and hypertension), stroke subtype, and stroke history (Terecoas a et al, 2022). Among individual factors, knowledge of stroke has been frequently documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation